The effect of psychological capital on work engagement: employee well-being as a mediator - Laila Meiliyandrie Indah Wardani; Suci Wulandari; Pratiwi Triasti; Agnis Sombuling (The Mattingley Publishing Co., Inc., 2020)
Human resourceshave an essential role as a factor that supports the success of the company, where companies are also required to prosper their workers then how workers can be attached to the company. In this study, work engagement is one of the factors, namely personal resources; some typical personal resources are in psychological capital that affects work engagement, such as self-efficacy and optimism. Then psychological capital also affects employee well-being, where one's positive condition influences the welfare of workers. Thus the employee well-being factor also influences work engagement with the welfare of good quality in the workplace. The purpose of this research is to find out the role of employee well-being as a mediator in the relationship between psychological capital and work engagement. Data analysis techniques in this study there is a mediation regression analysis of model 4 by Hayes. Respondents in this study were 235 private company workers in Greater Jakarta. The results of this study indicate there isa role of employee well-being as a mediator in the relationship between psychological capital with work engagement. The study conducted to cover the gap in the previous research.